The relationship between training program and emotional intelligence with training effectiveness - Syamsul Huda; Widodo Sunaryo; Martinus Tukiran; Nancy Yusnita; Idarianty Idarianty; Sumirah Sumirah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
Training effectiveness is one of the determinant factor that could improve employees’ job performance. When we found in a government district office at Jambi Province where the organization had provided many training program to the employees but it had not had significant impact on their employees’ job performance. We realized that we need to study the factors which assumed to have relationship with the training effectiveness. Prior research in training effectiveness found that employees perceived toward the training program designed by organization and individual employees’ emotional intelligence had influence the training effectiveness. Based on those findings we formulated the aim of this study that is to investigate the relationship between the training program and employees’ emotional intelligence with the training effectiveness. This study designed as a quantitative research used sample of 209 employees derived by random sampling from its population. This study utilized questionnaires as instruments to collect empirical data. The correlational analysis technique used to analyze the data. This study had generated findings that there were strong relationship between the training program and employees’ emotional intelligence with training effectiveness.